Bartter syndrome - report of an unusual late presentation case and brief review - Costa,Bernardo M (2016)
Bartter syndrome is a rare autosomal recessive condition caused by the inability of the thick ascending limb to reabsorb filtered sodium and chloride. Types I and II, called antenatal Bartter syndrome, are the most severe, and manifest in-utero as polyhydramnios, preterm labour, salt wasting, life-threatening volume depletion, and severe hypokalemic metabolic alkalosis, with a high early mortality rate if untreated. Type III is called classic Bartter syndrome and is usually milder and often diagnosed later, in early adolescence. Type IV is as severe as types I and II, but courses with sensorineural deafness. Type V is the latest entry to the Bartter-like syndromes. The defective transporter proteins responsible for these subtypes have been identified and their mutations have been characterized using genetic sequencing and in vitro heterologous expression models. We present an unusual case of a very late diagnosis of an attenuated type IV Bartter syndrome. Our suspicion of the G47R mutation in the ß-subunit (Barttin) of the ClC-K chloride channels was confirmed by genetic sequencing. This is a second unrelated case in our centre. Although there is significant variability in the presentation of some subtypes of Bartter syndrome, there is still a strong genotype-phenotype correlation in some mutations, like the one we present here. The acknowledgement of this has provided insight into the genetic and molecular mechanisms of the disease